Analisis Pengaruh Faktor Demografi, Upah Kerja, Motivasi Kerja dan Stres Kerja Terhadap Kinerja Guru SLB Swasta di Cirebon - Riefsy Arien Majidah Rahmawati Hakim; Ekawati Ekawati; Ida Wahyuni (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2019)
Preliminary study results showed there was stress symptomps on private SLB teachers in Cirebon such as fatigue and irritability. Stress symptomps could offend the teachers from completing their works because of not optimal, then their performance could be worsen. In carrying out their duties, they (for teachers who had been certified) were monitored by the government with the DP3 program while they (for those who have not been certified) had motivation such as finding work experiences and increasing soft skills. However, there were many teachers who didn’t have good hopes, so their efforts were not optimal yet, thus their performances could be worsen. Demographics factors and wages that received by teachers also variatives, so it could affect their performances. The purpose of this study was to analyze the demographic factors, wages, work motivation and work stress on the performance of private SLB teachers in Cirebon. This research used quantitative method with cross sectional study. The results showed that demographic factors didn’t effect teachers’ performance (sig. 0.358 for sex, sig. 0.420 for years of service). Wages didn’t effect teachers’ performance (sig. 0.680). Work motivation effected teachers’ performance (sig. 0.006). Job stress didn’t effect teachers’ performance (sig. 0.618). The conclusion of this study was work motivation effected the performance of private SLB in Cirebon teachers. Suggestions from this research were the school can improve teachers’ work motivations by giving awards in the form of certificates/incentive for teachers who have good performance, and create a good and conducive work environment.